(untitled) (Web of Teachers: Inderscience Research, 2025)
In this article, psychological properties of the development of communicative compensations of cadets are analyzed. Compensation is a set of psychological strategies used to overcome difficulties or restrictions, and it is important in forming effective communication skills of cadets. In the article, individual psychological factors in the development of communicative compensation, motivation, emotional, and communication skills were studied. The cadets also considered ways to increase the methods of eliminating uncertainties in communication and their effectiveness. The results of the study include recommendations to further strengthen the cadres and increase their psychological training.